2009
DOI: 10.1111/j.1939-1676.2008.0226.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Firocoxib and Tepoxalin on Healing in a Canine Gastric Mucosal Injury Model

Abstract: Background: Little is known about the effect of dual cyclooxygenase (COX) and lipoxygenase inhibition on canine gastric mucosal healing.Objective: This study compares the effects of putative dual COX and 5-lipoxygenase inhibition with that of COX-2 selective inhibition on gastric mucosal lesion healing in dogs.Animals: Six normal adult mixed-breed research dogs. Methods: Gastric body and pyloric lesions were induced by endoscopic biopsy. Dogs were treated with tepoxalin, firocoxib, or placebo for 7 days in a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 36 publications
(36 reference statements)
0
26
0
Order By: Relevance
“…Studies conducted in rats (Knight et al, 1996), chickens (De Boever et al, 2009), rabbits (Pollock et al, 2008), dogs (Knight et al, 1996;Homer et al, 2005) and humans (Waldman et al, 1996) reported that the parent compound reached maximum plasma concentrations in a variable time (0.7-4 h), and was rapidly converted to the active metabolite RWJ-20142. The dual activity of tepoxalin and the potent COX-1 activity inhibition of its metabolite have been demonstrated in different studies (Argentieri et al, 1994;Willburger et al, 1998;Goodman et al, 2009), and the long plasma half-life of the active metabolite allows once-a-day dosing (Homer et al, 2005). According to Waldman et al (1996), only tepoxalin (and not RWJ-20142) contributes to 5-LO inhibition.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Studies conducted in rats (Knight et al, 1996), chickens (De Boever et al, 2009), rabbits (Pollock et al, 2008), dogs (Knight et al, 1996;Homer et al, 2005) and humans (Waldman et al, 1996) reported that the parent compound reached maximum plasma concentrations in a variable time (0.7-4 h), and was rapidly converted to the active metabolite RWJ-20142. The dual activity of tepoxalin and the potent COX-1 activity inhibition of its metabolite have been demonstrated in different studies (Argentieri et al, 1994;Willburger et al, 1998;Goodman et al, 2009), and the long plasma half-life of the active metabolite allows once-a-day dosing (Homer et al, 2005). According to Waldman et al (1996), only tepoxalin (and not RWJ-20142) contributes to 5-LO inhibition.…”
Section: Introductionmentioning
confidence: 97%
“…Agnello et al (2005) showed that in dogs administration of 10 mg/kg of tepoxalin once daily for 10 days significantly reduced PGE2 production but not LTB4. In the dog, tepoxalin has been shown to be effective and safe in its therapeutic range (Goodman et al, 2009) after single (Homer et al, 2005) and repeated (Knight et al, 1996) administrations. Tepoxalin has been experimentally used in chickens at high dosages (30 mg/kg) with no adverse effects reported (De Boever et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Adverse gastrointestinal events reported in dogs, cats, and horses range from mild inflammation to catastrophic ulceration and death (Hough et al, 1999;Lascelles et al, 2005a;Lascelles et al, 2007). Because COX-2 is necessary for mucosal healing, the more specific a drug is for COX-2 the more likely it is to cause gastrointestinal ulceration and prevent healing of pre-existing lesions (Goodman et al, 2009). Gastrointestinal lesions caused by NSAIDs in dogs tend to be located in the pyloric antrum, and have a poor prognosis if not identified and treated early (Lascelles et al, 2005a).…”
Section: Effects On the Gastrointestinal Tractmentioning
confidence: 99%
“…Side effects of NSAIDs are related to their specificity to inhibit COX enzymes, including COX-1 and COX-2 [2730]. Currently, selective NSAIDs, which inhibit only COX-2, are preferable because they result in fewer side effects on kidneys and platelet aggregation [25] and less gastrointestinal irritation [1527]. …”
Section: Introductionmentioning
confidence: 99%